2023
DOI: 10.3390/molecules28031247
|View full text |Cite
|
Sign up to set email alerts
|

Rare Missense Variants of the Human β4 Subunit Alter Nicotinic α3β4 Receptor Plasma Membrane Localisation

Abstract: α3β4 nicotinic acetylcholine receptors (nARs) are pentameric ligand-gated cation channels that function in peripheral tissue and in the peripheral and central nervous systems, where they are critical mediators of ganglionic synaptic transmission and modulators of reward-related behaviours. In the pentamer, two α3β4 subunit couples provide ligand-binding sites, and the fifth single (accessory) subunit (α3 or β4) regulates receptor trafficking from the endoplasmic reticulum to the cell surface. A number of rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Our data indicate that the spatial localization of the molecular elements, along with the stimulation of nicotinic receptors, plays a crucial role in improving the secretory response, supporting the idea that nicotinic receptors promote the co-localization of VDCCs and vesicles to prepare the cell to release a huge volume of catecholamines in case of vital situations, as hypothesized in some works [6,29], and in accordance with the vision of the cytoskeleton as a dynamic structure modulating exocytosis [10,30]. Moreover, it has been reported that mutations in nicotinic receptors could alter their localization and functioning [31], leading, for example, to the dysregulation of the stress response in knockout mice [32].…”
Section: Discussionmentioning
confidence: 53%
“…Our data indicate that the spatial localization of the molecular elements, along with the stimulation of nicotinic receptors, plays a crucial role in improving the secretory response, supporting the idea that nicotinic receptors promote the co-localization of VDCCs and vesicles to prepare the cell to release a huge volume of catecholamines in case of vital situations, as hypothesized in some works [6,29], and in accordance with the vision of the cytoskeleton as a dynamic structure modulating exocytosis [10,30]. Moreover, it has been reported that mutations in nicotinic receptors could alter their localization and functioning [31], leading, for example, to the dysregulation of the stress response in knockout mice [32].…”
Section: Discussionmentioning
confidence: 53%